Using gas-solid mixture conservation laws for volcanic eruptions - Touma, R. (2013)
This paper presents further validation of previous works [1, 2] on simulating fully hyperbolic and fully conservative gas-solid mixture PDEs. Such a system allows non-equilibrium processes between the two phase systems and facilitates explosive volcanic eruption investigations. Resolutions for this system are presented and compared with other numerical methods demonstrating the fundamental physical and numerical significances to the relative motion within volcanic eruptions.